Phenolic acids in fermented foods: microbial biotransformation, antioxidant mechanisms, and functional health implications - Kumar, Anand; Saranyadevi, S.; Thirumalaisamy, Selva Kumar; Dapana Durage, Tharindu Trishan; Jaiswal, Swapnil Ganesh; Kavitake, Digambar; Wei, Shuai (Frontiers in Molecular Biosciences, 2025)
Phenolic acids, a heterogeneous group of plant polyphenols that play a significant role in health due to their antioxidant, anti-inflammatory, and disease-modulating activities. Historically, fermentation has been recognized as a versatile biotechnology for increasing the bioavailability and efficacy of phenolic acids in foods. During microbial fermentation, indigenous and bound phenolics are subjected to extensive biotransformation by lactic acid bacteria, yeasts, and other functional microbes. These microorganisms synthesize hydrolytic and oxidative enzymes, including esterase, decarboxylase, and phenolic acid reductase, which release and alter phenolic acids, such as ferulic, p-coumaric, caffeic, and gallic acids, from plant cell wall matrices. Microbial conversion increases solubility, changes structural components, and enhances antioxidant capacity. Mechanistically, phenolic acids exhibit potent radical scavenging, metal-chelating, and singlet oxygen-quenching activities that play a significant part in reducing oxidative stress and redox homeostasis. Structure-activity relationships demonstrate that hydroxylation and methoxylation patterns have a critical impact on antioxidant strength. Additionally, phenolic acids involve numerous molecular methods, such as the activation of Nrf2–ARE, suppression of NF-κB, followed by the restoration of gut barrier integrity results in the anti-inflammatory, neuro-, cardio-protective, and immunomodulatory. The coactive interactions within phenolic acids, bacterial metabolites like short-chain fatty acids (SCFAs), as well as the components of the food matrix further strengthen their biological activity. Our review highlights the critical study of bacterial biotransformation of phenolic acids during fermentation, explicates their antioxidant mechanisms, and highpoints their emerging importance for functional health. Insights into these interrelationships are vital for the development of functional fermented foods, which enhance the therapeutic effect of managing chronic diseases and promote overall health.